2008
DOI: 10.1143/jjap.47.872
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability and Electrical Characteristics of Tungsten Nitride Gates in Metal–Oxide–Semiconductor Devices

Abstract: Tungsten nitride (WN x) was investigated to be used as a metal gate of metal-oxide-semiconductor field effect transistors (MOSFETs). WN x films with various N/W atomic ratios were deposited on SiO 2 and HfO 2 by reactive sputter deposition at different N 2 /Ar ratio flows. Nitrogen concentration in WN x films increases rapidly with the N 2 /Ar gas ratio and tends to saturate. WN x films with nitrogen atomic ratio higher than 44% have a main phase of WN, and the WN phase is stable up to 800 C. The higher-order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…δ−WN shows excellent conductive characteristics with a low electrical resistivity of 9.964 × 10 –7 Ω·m. It is reported that tungsten nitride has attracted considerable attention in modern very large scale integrated circuits (VLSI) as a diffusion barrier between Cu and Si substrate because of its low resistivity, easy patterning, and compatibility with conventional complementary metal-oxide-semiconductor (CMOS) technology. , The low electrical resistivity of δ−WN suggests that δ−WN is a promising candidate for use as a diffusion barrier.…”
Section: Resultsmentioning
confidence: 99%
“…δ−WN shows excellent conductive characteristics with a low electrical resistivity of 9.964 × 10 –7 Ω·m. It is reported that tungsten nitride has attracted considerable attention in modern very large scale integrated circuits (VLSI) as a diffusion barrier between Cu and Si substrate because of its low resistivity, easy patterning, and compatibility with conventional complementary metal-oxide-semiconductor (CMOS) technology. , The low electrical resistivity of δ−WN suggests that δ−WN is a promising candidate for use as a diffusion barrier.…”
Section: Resultsmentioning
confidence: 99%
“…We can speculate that these bumps correspond to bubbles filled with nitrogen gas, in accordance with previous results reported for similar metal nitrides. 32 The bubbles are more clearly visible for the sample annealed at 300°C right underneath ͑B͒ as well as, on the film surface ͑A͒ ͓see Fig. 6͑a͔͒.…”
Section: Morphological Characterizationmentioning
confidence: 97%
“…Due to their low resistivity, appropriate work function, and thermal stability, refractory metal nitrides have been proposed for a number of applications, ranging from wafer level hermetic sealing 1 to field effect transistor (FET) gate electrodes. 2 In particular, the tungsten-based materials WN x and WN x C y have been considered as an alternative for both diffusion barriers 3,4 and gate electrodes 5 due to their low resistivity, appropriate and tunable work function (4.39-5.01 eV 6 ), thermal and mechanical stability, good barrier performance, and processing simplicity. 7,8 Depositions of WN x and WN x C y typically use ammonia and WCl 6 , WF 6 or W(CO) 6 as co-reactants.…”
mentioning
confidence: 99%